Comprehensive evaluation of S-glyco-modification in vitro based on the potential impacts to Michael addition - Wang, Menghe; Zhang, Yang; Chu, Songshen; Wang, Miao; Wang, Jiajia (Bioorganic chemistry, 2025)
S-glyco-modification referring to the non-enzymatic glycosylation of cysteine residues in proteins with acetylated unnatural monosaccharides, poses challenges to the specificity and validity of metabolic labeling techniques. The process of S-glyco-modification mainly involves Michael addition, however, influence factors related to such reaction are not well investigate. Herein, we investigated the potential impacts on Michael addition including temperature, pH, incubation time, and hydrolases in the cell lysates to the generation of S-glyco-modification. With the classical probe Ac4GalNAz as a control, we selected three existing GalNAz analogues, 1,6-Pr2GalNAz, Ac34deoGalNAz and But4GalNAz for a comprehensive evaluation. Our results demonstrate that higher temperature, longer incubation time and the presence of hydrolases remarkably promote the labeling effects of S-glyco-modification, however, only Ac4GalNAz is liable to basic pH condition with enhanced labeling signals. Of note, 1,6-Pr2GalNAz performs as an excellent candidate without unexpected labeling when exposed to various exploratory conditions, further indicating 1,6-Pr2GalNAz is the best choice, so far, to selectively label O-GlcNAcylated proteins. The discoveries in this paper provide comprehensive strategies to investigate the occurrence of S-glyco-modification during the metabolic labeling experiments with various of newly developed probes. In this paper, we selected four representative MCRs to subject various potential influence factors on thia-Michael addition for investigating the relationships between S-glyco-modification and MCRs. [Display omitted] •Potential influence factors on thia-Michael addition including temperature, pH, incubation time, and hydrolases are examined to the generation of S-glyco-modification.•1,6-Pr2GalNAz is the most excellent candidate without unexpected labeling when subjected to various exploratory conditions.